Ground Improvement in Deep Waters Using Dynamic Replacement - Hamidi, Babak; Nikraz, Hamid; Yee, K.; Varaksin, S.; Wong, L. (ISOPE, 2010)
Dynamic Replacement is a ground improvement technique used for treating soft compressible cohesive soils. It has been used in numerous land projects and a number of offshore works with seabed as deep as 15 m below sea level. Recently, works of similar nature was carried out in Southeast Asia with the intention of exploring the possibility of treating soils in deeper waters. In this case, the seabed was 30 m below sea level, and to the knowledge of the authors, is a world record as the deepest Offshore Dynamic Replacement or Dynamic Compaction works. The pressuremeter test was used to verify the results and to estimate the soil parameters.